The Arabidopsis thaliana Knockout Mutant for Phytochelatin Synthase1 (cad1-3) Is Defective in Callose Deposition, Bacterial Pathogen Defense and Auxin Content, But Shows an Increased Stem Lignification - De Benedictis, Maria; Brunetti, Cecilia; Brauer, Elizabeth K.; Andreucci, Andrea; Popescu, Sorina C.; Commisso, Mauro; Guzzo, Flavia; Sofo, Adriano; Ruffini Castiglione, Monica; Vatamaniuk, Olena K.; Sanità di Toppi, Luigi (Frontiers in Plant Science, 2018)
The enzyme phytochelatin synthase (PCS) has long been studied with regard to its role in metal(loid) detoxification in several organisms, i.e., plants, yeasts and nematodes. It is in fact widely recognized that PCS detoxifies a number of heavy metals by catalysing the formation of thiol-rich oligomers, namely phytochelatins, from glutathione and related peptides. However, recent investigations have highlighted other possible roles played by the PCS enzyme in the plant cell, e.g. the control of pathogen-triggered callose deposition. In order to examine novel aspects of Arabidopsis thaliana PCS1 (AtPCS1) functions and to elucidate its possible roles in the secondary metabolism, metabolomic data of A. thaliana wild-type and cad1-3 mutant were compared, the latter lacking AtPCS1. HPLC-ESI-MS analysis showed differences in the relative levels of metabolites from the glucosinolate and phenylpropanoid pathways between cad1-3 and wild-type plants. Specifically, in control (Cd-untreated) plants, higher levels of 4-methoxy-indol-3-ylmethylglucosinolate were found in cad1-3 plants vs. wild-type. Moreover, the cad1-3 mutant showed to be defective in the deposit of callose after Cd exposure, suggesting that AtPCS1 protects the plant against the toxicity of heavy metals not only by synthesizing PCs, but also by contributing to callose deposition. In line with the contribution of callose in counteracting Cd toxicity, we found that another callose-defective mutant, pen2-1, was more sensitive to high concentrations of Cd than wild-type plants. Moreover, cad1-3 plants were more susceptible than wild-type to the hemibiotrophic bacterial pathogen Pseudomonas syringae. The metabolome also revealed differences in the relative levels of hydroxycinnamic acids and flavonols, with consequences on cell wall properties and auxin content, respectively. First, increased lignification in the cad1-3 stems was found, probably aimed at counteracting the entry of Cd into the inner tissues. Second, in cad1-3 shoots, increased relative levels of kaempferol 3,7 dirhamnoside and quercetin hexoside rhamnoside were detected. These flavonols are endogenous inhibitors of auxin transport in planta; auxin levels in both roots and shoots of the cad1-3 mutant were in fact lower than those of the wild-type. Overall, our data highlight novel aspects of AtPCS1 functions in A. thaliana.